2005
DOI: 10.32398/cjhp.v3i4.1778
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Low-Fat Milk Consumption in a Multi-Ethnic Population

Abstract: Objective: To assess the correlates of low-fat milk consumption in a multi-ethnic population. Design: Cross-sectional random digit dial telephone survey of adults residing in Hawaii. Setting & Participants: The survey was completed by 600 adults who consumed cow’s milk. Five ethnicities composed over 86% of the sample: Caucasian (36%), Hawaiian (17%), Japanese (18%), Filipino (10%), and Chinese (5%). The average age of participant was 45.6. 84% had completed high school and 35% had completed college. Varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
0
6
0
2
Order By: Relevance
“…It is well documented that low-fat milk use declines with household income and educational attainment (Davis et al, 2012; Kitt et al, 2011; Maglione, Barnett, & Maddock, 2005). Davis, Dong, Blayney, Yen, and Stillman (2012) documented annual household income of less than US$20,000 influenced whole and 2% milk purchases.…”
Section: Background and Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that low-fat milk use declines with household income and educational attainment (Davis et al, 2012; Kitt et al, 2011; Maglione, Barnett, & Maddock, 2005). Davis, Dong, Blayney, Yen, and Stillman (2012) documented annual household income of less than US$20,000 influenced whole and 2% milk purchases.…”
Section: Background and Literaturementioning
confidence: 99%
“…Kitt et al (2011) findings provide strong evidence that low-fat milk use among low-income populations is one third that of the overall population. Moreover, it is well documented that use of low-fat milk progressively declines with lower levels of educational attainment (Davis et al, 2012; Maglione et al, 2005).…”
Section: Background and Literaturementioning
confidence: 99%
“…Аналогичные наблюдения отмечены в исследовании, проведенном среди взрослого населения государства Филиппины, в котором японцы, проживающие в регионе, чаще употребляли молоко низкой жирности в отличие от коренных жителей, которые чаще выбирали высокожировые виды молока (почти 79%) [7].…”
Section: Discussionunclassified
“…В ряде исследований [6] было отмечено, что на формирование привычек питания оказывают влияние разнообразные социально-экономические, географические и культурные факторы. Так, профиль потребления молочных продуктов среди разных этнических групп в рамках одной страны значительно отличается -это касается не только частоты потребления, но и выбора уровня жирности молочных изделий [7]. В связи с тем, что в странах Содружества Независимых Государств (СНГ) достаточно крупные популяции русской национальности длительно проживают в социально-культурных, природных условиях этих стран, данный регион представляет возможность для изучения роли этнических различий в потреблении молочных продуктов.…”
unclassified
“…A survey of Australian shoppers revealed poor milk nutrition knowledge, and there was evidence suggesting that some believed that low-fat milk contained fewer vitamins and minerals than whole milk (Bus & Worsley, 2003). Several studies found that there was little interest in changing to low-fat milk (Maglione, Barnett, & Maddock, 2005; Tuorila, 1987; WestGroup, 2009).…”
mentioning
confidence: 99%